1979
DOI: 10.1002/ijc.2910230517
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of in vivo immunity to tumor‐specific transplantation antigens of chemically induced murine fibrosarcomas

Abstract: A possible genetic control of the in vivo immunity to tumor‐specific transplantation antigen (TSTA) of two methylcholanthrene‐induced BALB/c fibro‐sarcomas, C‐1 and ST2, was studied in F1 compatible hosts. Both tumors, which have been previously shown to share their TSTA, lost their immunogenicity in (BALB/c×C3Hf)F1 and C‐1 also in (BALB/c×BALB.K)F1 mice; the immunogenicity of both sarcomas remained unchanged in other hybrid combinations of BALB/c with H‐2b or H‐2a animals. For C‐1 this was true either for a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1979
1979
1981
1981

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The loss of TSTA immunogenicity of ST2 in (BALBlc X C3Hf) and (BALB/c X C3H.OH) F1 mice, in fact, was not sufficient to conclude for a sharing of determinants between TSTA and alien non-H-2 antigens since we have recently found that a genetic control of anti-TSTA immunity exists and that (BALBlc X C3Hf) and (BALBlc X C3H.OH) hybrids are among low-responder animals (Parmiani and Ballinari, 1979).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The loss of TSTA immunogenicity of ST2 in (BALBlc X C3Hf) and (BALB/c X C3H.OH) F1 mice, in fact, was not sufficient to conclude for a sharing of determinants between TSTA and alien non-H-2 antigens since we have recently found that a genetic control of anti-TSTA immunity exists and that (BALBlc X C3Hf) and (BALBlc X C3H.OH) hybrids are among low-responder animals (Parmiani and Ballinari, 1979).…”
Section: Discussionmentioning
confidence: 90%
“…The F, study showed that (BALBlc X C3Hf) and (BALBlc X C3H.OH) and, to a lesser extent (BALBk X C3H.SW) mice, developed a lower anti-TSTA immune response than did BALB/c mice. This apparent hierarchy of low responsiveness introduced by genes of the C3H background may be due to a regulatory role of H-2 genes on the transplantation immunity to TSTA as suggested by studies on the genetic control of the in vivo immunity to other tumors (Williams et al, 1975;Albright et al, 1977;Parmiani and Ballinari, 1979;Forni et al, 1980). The significant response of (BALBlc X C3H.SW) F, animals to ST2, however, suggested that the minor alien antigens of C3H background do not include a relevant part of TSTA determinants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The suggestion was made, however, that the tumour-specific antigens of a number of immunogenic murine tumours might be alloantigens foreign to the syngeneic host (Invernizzi and Parmiani, 1975;Parmiani and Invernizzi, 1975;Parmiani, 1977). These studies showed that immunization with some allogeneic tissues could protect against the growth of the syngeneic tumour and that the converse also occurred, i.e.…”
Section: Discussionmentioning
confidence: 99%